Forests buffer against variations in precipitation. (28th July 2021) - O'Connor, John C.; Dekker, Stefan C.; Staal, Arie; Tuinenburg, Obbe A.; Rebel, Karin T.; Santos, Maria J.
Abstract: Atmospheric moisture recycling effectively increases the amount of usable water over land as the water can undergo multiple precipitation–evapotranspiration cycles. Differences in land cover and climate regulate the evapotranspiration flux. Forests can have deep roots that access groundwater facilitating transpiration throughout the dry season independent of precipitation. This stable transpiration buffers the forest against precipitation variability. However, it is not known whether the buffering effect, already modeled for tropical forests, is common to all forests globally. Here we apply a state‐of‐the‐art Lagrangian moisture tracking model (UTrack) to study whether forest land cover in the upwind precipitationshed can lead to a reduction in monthly precipitation variability downwind. We found a significant buffering effect of forests in the precipitation variability of 10 out of 14 biomes globally. On average, if 50% of precipitation originates from forest, then we find a reduction in the coefficient of variation of monthly precipitation of 60%. We also observed that a high fraction of precipitation from non‐forest land sources tends to have the opposite effect, that is, no buffering effect. The average variation of monthly precipitation was 69% higher in areas where 50% of precipitation originates from non‐forest land sources in the precipitationshed. Our results emphasize the importance of land cover composition in the precipitationshed to buffer precipitation variability downwind, in particular forest cover. Understanding the influence of land cover in a precipitationshed on atmospheric moisture transport is key for evaluating an area's water‐climate regulatory ecosystem services and may become increasingly important due to continued changes in land cover and climate change. Abstract : Precipitation originates from evapotranspiration in the upwind region known as the precipitationshed. The precipitationshed is unique for each area and can be composed of a combination of ocean, forest and non‐forest land covers. We found that areas with a higher fraction of precipitation originating from forests had lower variability in monthly precipitation while precipitationsheds largely composed of non‐forest land covers had higher variability in precipitation. Our study further demonstrates the important climate regulatory services provided by forests globally.